(untitled) (Bangladesh Journal of Botany, 2025)
This paper constructs a controllable environmental chamber to program and simulate the compound stress of high temperature, drought and aphids, and dynamically regulates the order and duration. RNA-Seq and LC-MS technology were combined to analyze leaf gene expression and metabolite changes, and monitor stomatal conductance and water use efficiency in real time. Field experiments were carried out in three ecological zones: arid, humid warm and temperate rain-fed, yield. The yield and biomass of 10 varieties were continuously monitored. Based on the random forest model, the environmental parameters, gene expression and yield data were integrated to construct a stress resistance prediction model to evaluate the adaptability of varieties under unknown stress combinations. The results showed that the comprehensive adaptability index (CRI) of climate-resistant varieties was generally higher than 0.6, the yield stability index (YSI) was between 30 and 47, the standardized photosynthetic efficiency (PER) was significantly better than that of general varieties, and the yield loss was lower. The study provides decision support and molecular tools for variety layout and stress resistance breeding. Bangladesh J. Bot. 54(2): 337-348, 2025(June)